2010
DOI: 10.1002/cncr.25513
|View full text |Cite
|
Sign up to set email alerts
|

Conservative and dietary interventions for cancer‐related lymphedema

Abstract: The findings support the use of compression garments and compression bandaging for reducing lymphedema volume in upper and lower extremity cancer-related lymphedema. Specific to breast cancer, a statistically significant, clinically small beneficial effect was found from the addition of manual lymph drainage massage to compression therapy for upper extremity lymphedema volume. Cancer 2011;117:1136-48. V C 2010 American Cancer Society.KEYWORDS: cancer-related lymphedema, dietary interventions, conservative inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
69
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 93 publications
(76 citation statements)
references
References 40 publications
3
69
0
4
Order By: Relevance
“…Moreover, previous systematic reviews only included conservative management of lymphoedema. [17][18][19] We also included a study on surgical management of LLL in this systematic review. 29 However, the included studies showed clinical heterogeneity and often included participants with LLL secondary to different aetiologies (Table 1 and Figure 2).…”
Section: Main Findings Strengths and Limitationsmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, previous systematic reviews only included conservative management of lymphoedema. [17][18][19] We also included a study on surgical management of LLL in this systematic review. 29 However, the included studies showed clinical heterogeneity and often included participants with LLL secondary to different aetiologies (Table 1 and Figure 2).…”
Section: Main Findings Strengths and Limitationsmentioning
confidence: 99%
“…Finally, long-term outcomes of lymphoedema treatment have rarely been investigated. [17][18][19] In 2010, the Core Outcome Measures in Effectiveness Trials (COMET) initiative was launched to develop agreed standardised sets of outcomes to represent the minimum set that should be measured and reported in all randomised trials of a specific condition. 31 We believe core outcomes set should be developed for future trials of LLL.…”
Section: Interventions and Comparisonmentioning
confidence: 99%
See 2 more Smart Citations
“…Another recent RCT has shown that early physical therapy (manual lymph drainage, scar tissue massage, active and active-assisted shoulder range of motion exercises) was effective in preventing lymphedema during the first year after surgery, 70 and a 2011 meta-analysis reported a significant benefit of manual lymph drainage when added to compression therapy in treatment of breast cancer-related lymphedema. 71 A 2010 Cochrane review reported that structured exercise during the postoperative period had significant short-term benefits in improving shoulder flexion range of motion, with physical therapy resulting in additional benefits for shoulder function. 72 Certainly, the breadth and quality of research available since the upper extremity rehabilitation and lymphedema guidelines were published underscore the need for them to be updated and revised to incorporate this evidence.…”
Section: Recommendations For Updates and Future Evidence-based Practimentioning
confidence: 99%